Potential Explanations for the Black-White Achievement Gap in U.S. Public Education - Hamadouche, Fatima (Journal of Human Sciences, 2018)
The present article probes into the magnitude of the black-white academic achievement gap and investigates the different probable explanations that laid the foundations for the academic discrepancies between black students and their more affluent counterparts in U.S. public education. In fact, the potential explanations that planted the seeds of the black-white achievement gap are dissimilar and varied. There is a wide range of factors and a huge array of miscellaneous explanations, or rather theories that can be held accountable for the present African American underachievement in U.S. public schools. The achievement gap issue necessitates a profound and strong comprehension of the gap’s grounds. There are no unanimously conventional causes of the black-white achievement gap. There is no consensus of what really caused the Black-white achievement gap in U.S. public education. In fact, explanations vary broadly along ideological, racial, and even political lines. Of the numerous explanations that have been provided, some are the outcome of scrupulous analysis and constructive study. Others stem from ideological- or some might consider them biased- positions. Indisputably, these beliefs and views are profoundly held. The explanations usually provided to account for the current gap spring from socio-cultural, socioeconomic, pedagogical, and genetic roots. Racism, genetic factors, black oppositional culture, socioeconomic and sociocultural attributes, and educational factors are mere possible explanations. We argue in this article that school-based factors are deemed as the most potential explanations for the black-white achievement gap in U.S. public education. We believe that operational educational practices can surmount all other problems and that all children can learn when provided with the proper pedagogical sustenance.